Fertility and fecundity rate in progesterone impregnated intravaginal sponge and eCG administered non-descript goats - C. Pugazharasi; T. Sarath; Cecilia Joseph; K. Kavitha; R. Sureshkumar; P. Veeramani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The efficacy of estrus synchronization for improving the fertility and fecundity was studied in 428 non-descript goats in Kanchipuram district (Tamil Nadu) selected based on clinical and ultrasound examination for synchronization. Non pregnant does were inserted with intravaginal progesterone sponge containing 300 mg of progesterone on day 0 and administered Inj. Cloprotenol sodium (Pragma) 125µg on day 10. The sponge was removed on day 11 of insertion followed by intramuscular injection of 200 I.U. of eCG (Inj.Folligon). Timed Artificial Insemination was done twice at 12 and 24 h interval using Tellicherry frozen semen. Among the synchronized does,359 does were confirmed pregnant by 30-45 days post insemination using transrectal ultrasonography with a conception rate of 83.87% and fecundity rate of 2.038. The study concludes that the progesterone based intravaginal sponge in combination with eCGcan be effectively used for estrus synchronization programme to improve conception rate and fecundity in non-descript goats at farmers flocks.